Pautas para la interacción entre la investigación y la extensión en la pesquería del camarón blanco (Penaeus spp.) en el Golfo de Nicoya, Costa Rica (ING) - Palacios, José Angel (1998)
A work guide is proposed to facilitate the coordination of research and social work in order to establish a link between researches, fishermen and those who execute the ordination policies of marine resources. The ultimate goal is to make research results available to the fisheries resource users. When these results are made accessible to the fishermen they will be able to develop an integral knowledge of the fisheries, from the biological aspects to the actual level of exploitation and ordination policies. In this way, a better under-standing of the exploited population will be obtained and future corrections on renovation rate of the resource and the exploitation rate will have a scientific base and will lead to biological sustainability.